Is the Social Capital Really Social? Deliberations on Jacek Tittenbrun’s “Neither Capital nor Class” - Grażyna Musiał (Экономическая социология, 2018)
Jacek Tittenbrun, a sociologist specializing in the sociology of economy, authored the book Neither Capital nor Class: A Critical Analysis of Pierre Bourdieu`s Theoretical Framework, for sociologists, economists, and researchers of other social disciplines (e.g., law, cultural studies, anthropology). In the book, written in the convention of critical realism methodology, Tittenbrun presents the scientific achievements of the well-known French sociologist, Pierre Bourdieu, an author who deals particularly with the concept of capital and capital issues. The French sociologist, who sometimes obscures the notion of capital and identifies opposing ownership relationships, is not attached to this book’s contributors, whose theses are expressed clearly.Tittenbrun sets a goal in this book to describe and explain the phenomena of capital and social classes. The research task formulated by Tittenbrun consisted of confronting those discovered in Bourdieu’s regularity, along with his construction of capital as an idea and selected, significant ideas about capital, proclaimed in modern science, mainly by Anglo-Americans. Tittenbrun acquaints readers with a wide and valuable spectrum of views, such as those of Gary Stanley Becker, Kenneth Joseph Arrow, Robert Merton Solow, and others.Tittenbrun makes no reference to the outstanding Russian sociologists who have chronicled the extensive achievements of Bourdieu, but the book is worth reading.